Whipple disease without joint involvement in a patient with chronic diarrhea and HIV seropositive partner: case report - Farias, Luis Arthur Brasil Gadelha; Lira, Mateus Lavor; Rocha, Matheus Dias Girão; dos Santos, Alessandra Marques; Silva Leitão, Terezinha do Menino Jesus; Girão, Evelyne Santana; Rodrigues, Jorge Luiz Nobre (Journal of Health & Biological Sciences, 2017)
Introduction: Whipple’s disease is a rare, infectious disease caused by the bacterium Tropheryma whipplei that affects multiple organs and systems. It is difficult to identifyand frequently presents as a diagnosis of exclusion due existence of conditions causing most prevalent chronic diarrhea, as AIDS and Inflammatory Bowel Disease. Case report: Herein we report the clinical findings of a 38-year-old male patient, married with a HIV seropositive woman, with a four-year course of chronic diarrhea until he received a definitive diagnosis. Treatment was started with a 15-day penicillin G regimen, followed by continued trimethoprim–sulfamethoxazole 80/400mg after hospital discharge up to current days. Conclusion: Currently, the patient remains asymptomatic and has completed clinical remission after two years of treatment.